Ethnopharmacological review of plants traditionally used in Darab (south of Iran) - Mahmoodreza Moein; Mohammad Zarshenas; Sedigheh Khademian; Amir Razavi (Shiraz University of Medical Sciences, 2015)
Aims: Ethnopharmacological and ethnobotanical information have been known as an effective tool for drug discovery. Iran is a location with long medical history. Darab is one of the cities in Iran that can be studied regarding ethnopharmacological aspects. Methods: current paper documented the folk medical information by Darab inhabitants. Therefore, field studies on this area were conducted from March to July 2012 and May to July 2013 under supervision of one local people. A questionnaire was utilized in this study and was filled by local inhabitants. Results: in total, 58 species belonging to 27 plant families were documented in management of 53 ailments. The most cited plant family was Asteraceae which was followed by Apiaceae, Lamiaceae and Papilionaceae. Herbs were applied for gynecologic and genitourinary, respiratory, central nervous system, infectious and cardiovascular ailments as well as musculoskeletal and skin disorders, respectively. Conclusion: this study can indicate the folk knowledge of a region in south of Iran, the knowledge that can easily disappeared during transition from old to new generations. Moreover, the effectiveness of unexamined plants can be evaluated according to informants' claims. Therefore, such investigations may be in deed, a useful way to search for drug discovery as well as keeping ethnopharmacological information alive.